Left Main Coronary Disease; Clinical Profile and Angiographic Characteristics - Ibrahim Shah , Mohammad Faheem , Shahzeb , Rafiullah, Mohammad Asif Iqbal, Mohammad Hafizullah (Journal of Rawalpindi Medical College, 2012)
Background: To analyze the clinical and angiographic characteristics of patients with left main coronary disease(LMCAD). Methods: In this descriptive study patients with left main coronary artery disease who underwent angiography were evaluated. Patients with left main coronary artery disease ranging from mild plaque to total obstruction were included. Clinical characteristics, risk factors and angiographic findings were recorded. Results: A total of 1422 (10.4%) left main disease cases were detected in which 953(6.99%) were non-obstructive or minimal and 468(3.43 %) were obstructive or significant. Patients with obstructive LMCAD had mean age of 56.32±6.34 years. Male and female were 68.16% and 31.83%, respectively. Diabetes mellitus (33.97%), hypertension (62.82%), dyslipidemia (53.84%) and smoking (36.96%) were main risk factors. Stable angina; FC ІІІ &ІV was seen in 16.88%, unstable angina in 71.79% and acute MI in 6.83%. On ECG, ST-elevation (>0.05 mV) in lead aVR was the commonest presentation (90.81%). Exercise ECG were positive for early angina in 90.81% and diffuse ischemia in 90.81%. Mean ejection fraction ±SD (%) was 48±8.45. Ostial, midshaft and distal end bifurcating disease was 20.94%,11.11% and 67.94%, respectively. In distal bifurcating LMCAD, LAD was involved in 56.40% and circumflex artery in 34.59%. Unprotected LMCAD was present in 3.1% and protected LMCAD in 0.33%. Conclusion: Age more than 50, unstable angina, diffuse ischemic changes on exercise electrocardiograms and coexistent triple vessels disease were the common denominators. Distal end of left main stem is the most common site affected.